Restoration of Cultural Landscapes in Spatial Planning = Problemy rewaloryzacji krajobrazu kulturowego w planowaniu przestrzennym - Kosieradzka, Angelika; Ludwig, Bogna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The issue of protection and development of the cultural landscape is an integral part of spatial planning at all levels. Progressing from the nineteenth century, interest in natural and anthropogenic landscape over the years has become the basis for conducting this research and the creation of a series of documents.
Keywords: planowanie przestrzenne; krajobraz kulturowy; ochrona krajobrazu; spatial planning; cultural landscape; landscape protection